2015
DOI: 10.1038/aps.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Associations of UDP-glucuronosyltransferases polymorphisms with mycophenolate mofetil pharmacokinetics in Chinese renal transplant patients

Abstract: The UGT2B7 11+985A>G genotype is associated with the pharmacokinetics of MPA in Chinese renal transplant patients, which demonstrates the usefulness of this SNP for individualizing MMF dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
22
2
Order By: Relevance
“…It was demonstrated that the opioid binding site in UGT2B7 is within the first 119 amino-terminal amino acids (N-terminal half of the protein) [61] . Polymorphisms in UGT2B7 showed significant association with MPA AUC in previously reported studies [62][63][64] . In our study, the UGT2B7 211G>T genotype was found to be an important factor that contributes to the variability in MPA pharmacokinetics.…”
Section: Discussionsupporting
confidence: 53%
“…It was demonstrated that the opioid binding site in UGT2B7 is within the first 119 amino-terminal amino acids (N-terminal half of the protein) [61] . Polymorphisms in UGT2B7 showed significant association with MPA AUC in previously reported studies [62][63][64] . In our study, the UGT2B7 211G>T genotype was found to be an important factor that contributes to the variability in MPA pharmacokinetics.…”
Section: Discussionsupporting
confidence: 53%
“…Clinical studies have shown that UGT1A8 gene polymorphisms not only affect the absorption and metabolism of MMF but also have a certain potential relation with the adverse effects of MMF. 19 However, for the same SNP locus, clinical conclusions have not been completely consistent. [20][21][22][23] This is mainly due to too many confounding factors that are difficult to rule out.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Xie et al. shown that the frequency of TT genotype was higher than Caucasian population [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Xie et al. reported that there were also no significant differences in either daytime and night time pharmacokinetics of MPA among UGT1A9 CC, CT, and TT genotype groups [ 22 ].…”
Section: Discussionmentioning
confidence: 99%